Development and optimization of passenger car front profile using polynomial response surface method - Kausalyah, Venkatason; Shasthri, Sivaguru; Abdullah, Kassim Abdulrahman; Mahmoud Idres, Moumen Mohammed; Shah, Qasim Hussain (Asian Research Publishing Network, 2016)
In most developed countries, the statistical data of road traffic accidents involving motor vehicle-pedestrian crashes have registered much cause for concern and consequently, a concerted effort by various sectors have for the past two decades been brought to bear towards mitigation efforts. Amongst the different approaches in this direction, it has been established that pedestrian kinematics during impact plays an important role in the ensuing injuries particularly to the head, and has been shown to have a direct bearing with the vehicle front-end shape. This has eventually led to some optimization efforts of the vehicle front-end geometry but due to the complex nature of the problem, many difficulties have been encountered and an exhaustive comprehensive solution has yet to be achieved. In a step towards an attempt in addressing some of these issues, this paper demonstrates the feasibility of an alternative method for developing an optimization friendly deformable vehicle structure, having simple, easily modifiable profile geometry requiring short processing time for the particular purpose of performing multi-parametric optimization of the vehicle front end shape with the goal of minimizing the sustained head injuries of the pedestrian. The proposed hybrid case model has successfully achieved an efficiency of 99.85% in CPU time in comparison to a full finite element model. The polynomial response surface method is employed to generate the mathematical models which in turn are used for the optimization process. The mathematical models developed are found to show acceptable predictive capabilities with the child model having the highest model fitness of 90.7%. The optimization is successfully able to find a front-end geometry which minimizes the HIC values for both the adult 50th percentile male pedestrian and the 6 year old child pedestrian. Finally, the study further reinforces the necessity for the consideration of the relationship that exists between pedestrian kinematics and vehicle front-end profile in design considerations as well as in development of further test procedures and safety mitigation methods.